ENVIRONMENTAL SUSTAINABILITY STRATEGIES ON THE MARKET PERFORMANCE OF MANUFACTURING COMPANIES - Denise Kirabo Nyakato (Uganda Christian University, 2024)
This study examined the effect of environmental sustainability strategies on the market performance of manufacturing companies with a focus on Nice House of Plastics. The study aimed to explore the role of waste reduction management, green transportation, and energy efficiency in enhancing market performance. The study integrated qualitative and quantitative research approaches using a mixed methods approach to thoroughly investigate these tactics. Interviews were used to gather data from 40 employees in different departments, guaranteeing a varied representation of viewpoints. The results showed that waste reduction management has a major positive impact on innovation and operational expenses, both of which improve market performance. Green transportation was found to be crucial for raising the company's status in the market by strengthening supply chain effectiveness, boosting brand recognition, and reducing the dangers connected with reliance on fossil fuels. Initiatives aimed at increasing energy efficiency have also been demonstrated to lower manufacturing costs, enhance operational stability, and foster innovation—all of which enhance market performance. The overwhelming agreement among those surveyed emphasizes the strategic significance of these sustainability efforts in preserving a competitive advantage in a market that is becoming more environmentally conscientious. Notwithstanding, the existence of certain discord and ambiguity highlights the want of sustained correspondence and involvement to guarantee that every staff member comprehends and values the advantages of these endeavours entirely. The study underscored the importance of integrating environmental sustainability strategies into the core operations of manufacturing companies, not only as a means of regulatory compliance but also as a driver of long-term market success. The study concluded that these strategies are instrumental in achieving sustainable growth and maintaining a competitive edge in an increasingly eco-conscious marketplace. It is recommended that manufacturing companies should invest in sustainable technologies and practices to improve their market performance. Further research should explore the long-term financial impacts of sustainability strategies and the role of government policies in supporting sustainable manufacturing.